Upaya peningkatan kesadaran preventif terhadap penyakit insomnia pada generasi milenial selama masa pandemi Covid-19 - Purnamasari, Septi; Laeto, Arwan Bin; Inggarsih, Rara; Diba, Masayu Farah (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Insomnia is a complaint in terms of difficulty initiating or maintaining or restorative sleep that lasts at least one month and causes impairment in individual functioning. Adolescent poor sleep patterns can also be caused by the use of electronic media (television, laptop, gadgets, computers, etc.) for a long duration, migraine, and smoking. The impact of sleep deprivation on adolescents can lead to decreased school academic performance, increased absenteeism, depression and traffic accidents. This community service activity is in the form of counseling and education about the cause of insomnia, the adverse effects that can occur, and efforts to prevent insomnia, promotive actions that can be taken, and assistance for independent sleep analysis and early detection so that insomnia disorders do not develop into worse types and cause other diseases through material presentation and discussion session. About 30 students of SMP IT Bina Ilmi Palembang have received benefits and solutions in the form of educational information about the cause, impact and preventive measures that can be taken to reduce the risk of insomnia which increases during the Covid-19 epidemic.